Terorisme di Lingkungan Kelompok Muslim - Abdul Majid (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Terrorism could be simply defined as an act that causes fear by doing  harassment to reach particular object. There are many factors contribute to the  emergence of terrorism such as religion, psychology, economic, politics, and social.  All of them could create any movement from nationalism-separatism, religious  fundamentalism, and new religion movement to Islamic radical-fundamentalism. But  none of them could indicate that Islam is identical to terrorism. Many think that terrorism is similar to jihad. As a religion that is bestowed to universe, it becomes  awkward when Islam is accused for being teaching and encouraging terrorism. Jihad  is not the other word of terrorism. Jihad is taken after passing a tight Islamic law  consideration. Differently to Jihad, terrorism is relatively without legal consideration.  Jihad respects human rights. In the order way around, terrorism disrespects human  rights. So that, Jihad is not the same to terrorism. What perceive them the same is  indeed narrow-minded or misconception toward ideal understanding about Islam.  Perhaps, there could be people using Islam for masking their faces in order to reach  their object.